Reutilización de lodos del proceso de anodizado de aluminio, generados en la planta de tratamiento de aguas residuales de la fábrica CEDAL, como materia prima para la elaboración de material decorativo como fachaletas en la provincia de Cotopaxi en el periodo abril-agosto 2022. - León Coque, Luis Ángel (2022)
The purpose of this research work is to reuse the sludge generated in the anodizing process as an alternative aggregate for the manufacture of decorative materials, in order to reduce the considerable amount of sludge, offering a second sustainable alternative for final disposal. The final disposal of the sludge requires large areas of land, leading to environmental problems. In addition to the large area requirement, other problems are the useful life of the site, the handling and treatment of the leachate generated. First, a CRTIB analysis of the sludge was performed to evaluate its toxicity. second, the façades were manufactured using different dosages of sludge (0-50%). finally, the mass balance, break-even point, net present value (NPV) and rate of return (IRR) were calculated. the main results showed that the sludge complied with the parameters indicated in the Mexican SEMARNAT 2005 regulations, classifying it as a non-toxic special waste. The results obtained show that it is possible to reuse the sludge as a second alternative for the final disposal of sludge, which would allow reducing the volume of sludge generation, saving costs of storage, transportation and final disposal of waste, and implementing a new production area. The use of the sludge for the removal of petroleum hydrocarbons is suggested.